Analysis of Indoor PM2.5 Contaminants Based on Outdoor Wind Velocity Through Different Infiltration Types - Ghaim Man Oo; Komsilp Kotmool; Mongkol Mongkolwongrojn (Journal of Engineering, 2025)
Nowadays, indoor PM2.5 concentrations have become a significant factor affecting indoor air quality (IAQ) and a major public concern, particularly with the rise of haze in Thailand and globally, as PM2.5 can penetrate human lungs. This research analyzes the dispersion of PM2.5 from outdoors to indoors using a fluid dynamics simulation framework that combines the Eulerian approach for continuous flow, the Lagrangian approach for particulate matter dispersion, and the RNG k‐ ε turbulent model for airflow. The study is aimed at protecting indoor environments from harmful exposure to PM2.5 from outdoor contaminants and improving IAQ. Primarily, three different infiltration types and shapes are studied to determine the minimum optimal positive room pressure, based on the impact of ambient wind velocity on indoor PM2.5 concentrations from outdoor pollutants. A minimum optimal pressure of 3.6 Pa and 27 air changes per hour (ACH) is sufficient to achieve a PM2.5‐free indoor environment for all infiltration models. Furthermore, higher wind speeds can reduce indoor PM2.5 concentrations due to the increased momentum of particles. This research technique is implemented in the practical field study conducted within the laboratory room of the 55‐Year Chalermprakiat Building. As a result, the investigated room, with an infiltration area of 0.06 m 2 and a rate of 0.0036 m 3 /s, will be certified as a clean room by achieving an optimal minimum pressure of approximately 0.01 Pa. This research will help achieve cleaner and safer indoor environments for any building by leveraging the optimal minimum pressure of cleanroom technology, provided that the infiltration rate and ambient wind velocity are accurately determined.
Keywords: Air Quality and Health Impacts; Wind and Air Flow Studies; Atmospheric chemistry and aerosols